Intensive Care Nurses' Experience of Caring in Greece; A Qualitative Study - Parissopoulos, Stelios; Timmins, Fiona; Mpouzika, Meropi; Mantzorou, Marianna; Kapadochos, Theodore; Papagaroufali, Eleni (My University, 2022)
Whilst nurses and critical care services have been at the forefront of the COVID-19 pandemic, it has become more apparent that intensive care nurses are presented with challenging ethical and clinical decisions and are required to care for individuals with critical illnesses under high-pressure conditions. This is not a new phenomenon. The aim of this study, which was conducted before the outbreak of COVID-19, was to explore the experience of caring through the narratives of intensive care nurses in Greece.
Keywords: ICU nurse; Caring; Empathy; Negotiation; Qualitative; Technology; Thematic analysis